Global justice and international affairs - Brooks, Thom. (Studies in Moral Philosophy, 2012)
Global justice and international affairs is perhaps the hottest topic in political philosophy today. This book brings together some of the most important essays in this area. The essays have all appeared recently in the Journal of Moral Philosophy , an internationally recognized leading philosophy journal. Topics include sovereignty and self-determination, cosmopolitanism and nationalism, global poverty and international distributive justice, and war and terrorism.